2013
DOI: 10.1093/jjco/hyt018
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Polymorphisms of rs693 and rs1042031 in Apolipoprotein B Gene With Risk of Breast Cancer in Chinese

Abstract: Background: Lipid synthesis is an integrated result of genetic, epigenetic and environmental factors, and also can promote growth and survival of cancer cells. Apolipoprotein B plays a central role in lipid metabolism as the major protein component of very-low-density lipoprotein and low-density lipoprotein. Methods: We investigated the associations of polymorphisms of rs693 (27673C.T) and rs1042031 (212669 G.A) in the APOB gene with risk of breast cancer in 675 bloodunrelated Chinese patients with breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, rs1042031 is a coding sequence variant that causes glutamate to lysine mutation (C > T), or the introduction of a stop codon in the amino acid sequence (C > A). The rs1042031 mutation is important for regulating the binding of apolipoprotein B to the LDL cholesterol receptor (Liu et al, 2013). In this work, these two mutations were found to be related to SONFH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rs1042031 is a coding sequence variant that causes glutamate to lysine mutation (C > T), or the introduction of a stop codon in the amino acid sequence (C > A). The rs1042031 mutation is important for regulating the binding of apolipoprotein B to the LDL cholesterol receptor (Liu et al, 2013). In this work, these two mutations were found to be related to SONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Both apolipoproteins are involved in lipid metabolism and cancer biology [1,71]. The investigation into the connections between apoB gene polymorphisms and BC risk reported by Liu et al concluded that polymorphisms, such as 12,669 GA and 7673 CT, significantly increase the risk of this tumor, particularly in women undergoing menopause [72]. Once breast carcinoma develops intraocular metastasis, apoB functions as a risk factor like apoA-I [65].…”
Section: Apob Apoc-i Apom and Bcmentioning
confidence: 99%
“…Though relative reports were not as many as apoAI, apoB is considered to have tumor-promoting effects. Liu et al found a correlation between polymorphisms of apoB gene and risk of breast cancer [ 21 ]. Cedó et al further found that apoB stimulated growth of estrogen receptor-positive breast cancer cells, via transporting 27-hydroxycholesterol [ 22 ].…”
Section: Discussionmentioning
confidence: 99%